Identifying the New and Practical Components and Dimensions of Entrepreneurship in the Banking Network with a Digital Technology Approach - Nobakht, Afshin; Nasiri, Majid; Saeedi, Parviz (International Journal of Innovation Management and Organizational Behavior (IJIMOB), 2025)
Objective: The aim of this study is to identify the components and dimensions of entrepreneurship within the banking network from a digital technology perspective. Methodology: This research is categorized as applied research, qualitative in nature, and employs a descriptive survey approach. The statistical population consists of all experts specializing in information technology and entrepreneurship within the banking industry. Following Strauss and Corbin’s guidelines, 15 participants were selected through snowball sampling. Data collection was conducted through both library research and fieldwork, utilizing semi-structured interviews. The interviews were analyzed using MAXQDA software and a systematic coding process, complemented by the fuzzy Delphi method. To enhance the reliability and validity of the questionnaire, preliminary consultations were held with academic professors, who reviewed and provided feedback on the questions. Subsequently, a subset of the statistical population was given the revised questionnaire to address and resolve any ambiguities, before distributing the final version. Cronbach’s alpha coefficient was employed to assess the reliability of the measurement instrument. Findings: The research findings indicate that the establishment and expansion of digital entrepreneurship by banks are influenced by various dimensions, including the development of financial technologies, the creation of e-business models, the provision of e-entrepreneurship facilities, e-commerce infrastructure management, digital currency and blockchain development, the adoption of digital entrepreneurship ideas, and the advancement of electronic banking. Conclusion: It can be concluded that these dimensions are potentially pivotal in forming a digital banking entrepreneurial network.